Macrophages Control the Bioavailability of Vitamin D and Vitamin D-Regulated T Cell Responses - Lopez, Daniel Villalba; Al-Jaberi, Fatima A. H.; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte Menné; Kongsbak-Wismann, Martin; Geisler, Carsten (Frontiers in Immunology, 2021)
The active form of vitamin D3 (1,25(OH)2D3) has a great impact on T cell effector function. Thus, 1,25(OH)2D3 promotes T helper 2 (Th2) and regulatory T (Treg) cell function and concomitantly inhibits Th1 and Th17 cell function. Thus, it is believed that vitamin D exerts anti-inflammatory effects. However, vitamin D binding protein (DBP) strongly binds both 1,25(OH)2D3 and the precursor 25(OH)D3, leaving only a minor fraction of vitamin D in the free, bioavailable form. Accordingly, DBP in physiological concentrations would be expected to block the effect of vitamin D on T cells and dendritic cells. In the present study, we show that pro-inflammatory, monocyte-derived M1 macrophages express very high levels of the 25(OH)D-1α-hydroxylase CYP27B1 that enables them to convert 25(OH)D3 into 1,25(OH)2D3 even in the presence of physiological concentrations of DBP. Co-cultivation of M1 macrophages with T cells allows them to overcome the sequestering of 25(OH)D3 by DBP and to produce sufficient levels of 1,25(OH)2D3 to affect T cell effector function. This study suggests that in highly inflammatory conditions, M1 macrophages can produce sufficient levels of 1,25(OH)2D3 to modify T cell responses and thereby reduce T cell-mediated inflammation via a vitamin D-mediated negative feed-back loop.